Representation of transmission lines: comparison of models and parameters distributed discrete parameters - Araujo, Anderson Ricardo Justo de [UNESP]; Silva, Rodrigo Cleber da [UNESP]; Kurokawa, Sergio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2013)
A transmission line is characterized by the fact that its parameters are distributed along its length. This fact makes the voltages and currents along the line to behave like waves and these are described by differential equations. In general, the differential equations mentioned are difficult to solve in the time domain, due to the convolution integral, but in the frequency domain these equations become simpler and their solutions are known. The transmission line can be represented by a cascade of π circuits. This model has the advantage of being developed directly in the time domain, but there is a need to apply numerical integration methods. In this work a comparison of the model that considers the fact that the parameters are distributed (Universal Line Model) and the fact that the parameters considered concentrated along the line (π circuit model) using the trapezoidal integration method, and Simpson's rule Runge-Kutta in a single-phase transmission line length of 100 km subjected to an operation power. © 2003-2012 IEEE.
Keywords: Cascade circuits; Distributed parameters; Electromagnetic transients; Lumped; Numerical integration methods; Transmission lines; Cascade circuit; Distributed parameter; Electro-magnetic transient; Numerical integration methods; Differential equations; Electric lines; Runge Kutta methods; Transmission line theory; Time domain analysis